Cloning of Drosophila choline acetyltransferase cDNA. - Itoh, N.; Slemmon, J.R.; Hawke, D.H.; Williamson, R.; Morita, E.; Itakura, K.; Roberts, E.; Shively, J.E.; Crawford, G.D.; Salvaterra, P.M. (Proceedings of the National Academy of Sciences of the United States of America, 1986)
Choline acetyltransferase (EC 2.3.1.6) is the biosynthetic enzyme for the neurotransmitter acetylcholine. To isolate choline acetyltransferase cDNA clones, a cDNA library was constructed from poly(A)+ RNA of Drosophila melanogaster heads, these being one of the richest known sources of the enzyme. By screening the cDNA library with a mixture of three different monoclonal antibodies to Drosophila choline acetyltransferase, we isolated 14 positive clones. Only 1 of these clones was identified to be a Drosophila choline acetyltransferase cDNA clone based on the following evidence. (i) The amino acid sequence deduced from the nucleotide sequence of the cDNA insert completely corresponded to that of several tryptic peptides from choline acetyltransferase. (ii) The cDNA insert hybridized specifically to only the region on Drosophila polytene chromosomes that had been identified as the site of the choline acetyltransferase (Cha) gene by cytogenetic analysis. The cDNA insert consisted of a coding region 2190 nucleotides long, a 3'-noncoding region 284 nucleotides long, and EcoRI linkers. RNA analysis of Drosophila head poly(A)+ RNA with the cDNA insert as a probe showed the choline acetyltransferase mRNA to be approximately equal to 4700 nucleotides long.